A study of PV soiling loss and angle of incidence in outdoor conditions - Bing Guo (25387) (2025)
Solar photovoltaic soiling loss is influenced by the angle of incidence of solar radiation. Quantifying this effect is critical for interpreting optical soiling sensor data and comparing soiling losses across different locations and time periods. Building on previous laboratory studies, this work presents outdoor experiments that measure both solar-tracking normal-incidence soiling loss and fixed-tilt soiling loss. The solar-tracking normal-incidence soiling loss results closely matched laboratory results. The previously developed Guo-Javed model accurately described the relationship between the normal-incidence soiling loss and the fixed-tilt soiling loss. It also reliably predicted irradiance-weighted daily soiling loss based on normal-incidence measurements. Furthermore, the model was used to isolate the angle of incidence effect and provide insight into seasonal variations in apparent dust potency. This study confirms the Guo-Javed model’s value in applications such as converting soiling sensor readings into daily PV soiling loss and establishes a practical, low-cost approach for measuring normal-incidence soiling loss using solar tracking. Other Information Published in: Solar Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.solener.2025.114253